Experience of preparing teachers for teaching children to swimming - A.A. Tretyakov,; E.S. Nikolaeva,; A.G. Chebotarsky,; A.Y. Golub, (Theory and Practice of Physical Culture, 2023)
Objective of the study was to identify organizational aspects related to the training of teachers to teach children to swim in the region. Methods and structure of the study. As part of achieving this goal, the literature and regulatory documents related to the organization of work in educational institutions of the Belgorod region for teaching children to swim have been analyzed. Results and conclusions. The results obtained indicate the formation of the necessary competencies among teachers. During the training under the developed advanced training program, in total, more than 250 people formed competencies in teaching children to swim. In turn, the formed competencies are successfully applied in the educational process of educational organizations.